2013
DOI: 10.1002/anie.201307547
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Unexpected Functional Inversion of a PqsR Antagonist in Pseudomonas aeruginosa: An In Vivo Potent Antivirulence Agent Targeting pqs Quorum Sensing

Abstract: The virulence regulator PqsR of Pseudomonas aeruginosa is considered as an attractive target for attenuating the bacterial pathogenicity without eliciting resistance. However, despite efforts and desires, no promising PqsR antagonist has been discovered thus far. Now, a surprising functionality change of a highly affine PqsR antagonist in P. aeruginosa is revealed, which is mediated by a bacterial signal molecule synthase and responsible for low cellular potency. Blockade of the susceptible position led to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 30 publications
5
92
0
2
Order By: Relevance
“…However, a subsequent synthetic modification of this molecule resulted in a strong PqsR antagonist in P. aeruginosa (2-heptyl-6-nitro-4-oxo-1,4-dihydroquinoline-3-carboxamide, Fig. 5D) [59,60]. More often however, the differences in activity in heterologous versus the target bacterium relate to a lack of internalization, active efflux, modification or toxicity of the hit compound.…”
Section: Discussionmentioning
confidence: 96%
“…However, a subsequent synthetic modification of this molecule resulted in a strong PqsR antagonist in P. aeruginosa (2-heptyl-6-nitro-4-oxo-1,4-dihydroquinoline-3-carboxamide, Fig. 5D) [59,60]. More often however, the differences in activity in heterologous versus the target bacterium relate to a lack of internalization, active efflux, modification or toxicity of the hit compound.…”
Section: Discussionmentioning
confidence: 96%
“…S5 in the supplemental material). The relative ineffectiveness of these analogues as PQS antagonists may in part be due to hydroxylation of HHQ analogues (H at C-3) to PQS analogues (OH at C-3), thus establishing the nonantagonistic behavior explained by a recent report by Lu and colleagues, where the action of PqsH rendered anti-PQS compounds ineffective through bioconversion (55).…”
Section: Fig 3 Microscopic Analysis Reveals Altered Biofilm Structurementioning
confidence: 90%
“…However, both HHQ and PQS are coinducers of the virulence-associated LysR-type transcriptional regulator PqsR (41). The structural moieties that underpin the interaction between HHQ/PQS and PqsR remain to be fully characterized, although recent studies have reported diverse classes of PqsR antagonists (53)(54)(55) and implicated the hydrophobic pocket situated within the PqsR protein (56). Therefore, in order to assess whether the lead compounds could elicit a virulence response from P. aeruginosa, phenazine production and pqsA promoter activity (57) were monitored in a pqsA mutant where the capacity to produce native HHQ and PQS had been lost.…”
Section: Fig 3 Microscopic Analysis Reveals Altered Biofilm Structurementioning
confidence: 99%
“…Moreover, P. aeruginosa uses a cell density-dependent cell-to-cell communication system that is referred to as 'quorum sensing' to coordinate group behavior such as the formation of biofilms and the production of virulence factors. Interfering with the quorum sensing systems by such new types of 'pathoblockers' -as an alternative to classic antibiotics -appears as a promising new approach to control infectious diseases without the risk of inducing bacterial resistance [78] and would be a really promising way to fight against this lung infection. Still, however, the delivery of such molecules and in particular through noncellular barriers such as mucus and bacterial biofilms remains limited.…”
mentioning
confidence: 99%